How certain historical times influenced the dinamics of migration? (Academic Journal of Internal Affairs, 2020)
Population movements have always played an important role in world history. The main question is how history affects migration and how migration influences history. The dynamic process of migration is considered as a tool for human adaptation. Previously, the migration decision was motivated mainly by looking for better chances, in the first decades of the 21st century people leave their home due to such immediate dangers like various effects of climate change, natural disasters and weakness of states, civil war situation within a country, that is lack of economic and security stability. Although, only 3.5 percent of the world population is concerned in international migration, those migrants are concentrated on certain continents, regions and some countries. Mobility is the main character of our contemporary history. However, the new old types of international migration can be seen, like temporary or circular migration, but these phenomena are not really new. We can find their parallel patterns in important historical times.
Keywords: mobility; migration; world history; refugees